KEBIJAKAN HUKUM PIDANA DALAM MENANGGULANGI TINDAK PIDANA MINERAL DAN BATUBARA (Studi Kasus Polda Jateng) - Dwi Edy Purnomo; Sri Endah Wahyuningsih (UNISSULA Semarang, 2017)
The purpose of this study: 1) To know and analyze the setting of criminal acts of minerals and coal in the current positive law. 2) To know and analyze the weaknesses of the mineral and coal crime settings in the current positive law. 3) To know and analyze criminal law policy in coping with minerals and coal crime in the future. Result of research: 1) Mining crime is a crime in a mining business conducted by an individual, a group of people, or a legal entity that in its operation does not have permission from government agencies in accordance with applicable regulations. 2) The Minerba Act contains 4 (four) contradictory weaknesses. 3) In addition to the provision of punishment in the form of fines, it would be nice if accompanied by a maximum penalty penalty. Keywords: Criminal Law Policy, Mineral and Coal Crime